Edible Spectrum: Design Consideration for the Tropics - Azmi, Mohammad Firas; Taib, Nooriati (MAJ - Malaysia Architectural Journal, 2020)
Our ability to feed our growing population is becoming increasingly concerned. Population trends suggest that by 2050 there will be 9.6 billion people on the planet, and food demand will increase by 60%. Using edible insects as an alternative source of protein for human food and animal feed is the best idea for a solution. However, the challenge is to integrate insects as human’s source of food and changing the human perceptions towards insect while educating human the importance of insect to the environment. The purpose of this study is to explore the design consideration of an insectarium in general. Four case studies of project in Malaysia and Southeast Asia are selected for this research: Entopia by Penang Butterfly Farm, Kuala Lumpur Butterfly Farm, Singapore Changi Airport’s Butterfly Garden and Bangkok Butterfly Garden and Insectarium. Comparative study was done based on the availability of information internet findings, some own experience and suggestions from expert and others. As a result, a recommendation for design consideration in designing an insectarium in tropical climate will be compared and discussed on their pros and cons. This outcome will be a reference and attention to the designers in applying the best condition of design requirement as well as design principles to a build insectarium.